Cryptanalysis Of The Advanced Encription Standard & Skip Jack - Phan, Raphael Chung We (2002)
Cryptography is a science of the principles and methods used in encryption, a way by which we protect our confidential information from the peering eyes of unauthorized individuals. Cryptanalysis complements cryptography as a study and analysis of the methods used in encryption. In this thesis, we focus our attention on the cryptanalysis of secret-key block ciphers. We present the reasons behind the need for cryptanalysis and then move to discuss the popular cryptanalysis method namely differential cryptanalysis, linear cryptanalysis, related-key cryptanalysis and truncated differential cryptanalysis upon which many new cryptanalysis method are based. The new Advanced Encryption Standard (AES), set to replace the popular Data Encryption Standard (DES) is analyzed. In particular we analyze the key schedule of the AES and illustrate a dedicated attact and impossible differential attack on the AES. We also present our results on the analysis of the MixColumn component of the AES and established some interesting properties about the impossible differentials of the AES. Finally we extend the amplified boomerang attact on block ciphers. We derive a higher-order differential-like property and propose a new extended attack called the amplified truncated boomerang attack based on this property. We demonstrate the elegance of this attack by applying it to Skipjack, a block cipher recently declassified by the US government. We also compare our attack with other existing and somewhat similar attacks such as the truncated differential attack, impossible differential attack, boomerang attack, and amplified boomerang attack.